Electrochemical Properties and Reactions of Organoboronic Acids in the Presence of Fluoride Ions. Issue 11 (7th July 2016) - Suzuki, Junji; Shida, Naoki; Inagi, Shinsuke; Fuchigami, Toshio
Abstract: Electrochemical analyses of alkyl, phenyl, and thienylboronic acids were comparatively studied by cyclic voltammetric measurements in the absence and presence of fluoride ions, and we found remarkable negative shift of their oxidation potentials in the presence of fluoride ions compared with those in the absence of fluoride ions. Such negative shift seems to be derived from the formation of negative charged boron‐ate complex with fluoride ions. Anodic fluorination of 2‐acetyl‐5‐thienylboronic acid was carried out to provide mono‐ and trifluoro products eliminating a boryl group in moderate yields. These results clearly indicate that a boryl group with fluoride ions is a good electroauxiliary. Abstract :